Groundwater composition fluctuation within technogenic zones (case study: flooded coal mines in Primorsky Krai, Russia) - Tarasenko, I.A.; Zinkov, A.V.; Vakh, E.A.; Vetoshkina, A.V.; Strelnikova, Anna Borisovna (IOP Publishing, 2016)
The paper considers groundwater composition fluctuation within technogenic zones based on evidence from the flooded coal mines of Primorye. The authors have determined the regularities of hydrogeochemical processes, specified the groundwater composition fluctuation within the technogenic complexes located in the liquidated mine areas, and identified the equilibrium phases between the studied waters and specific secondary minerals. It has been proved that water within natural-technogenic complexes in the liquidated mine areas are saturated with silicates, carbonates, sulfates, oxides, and hydroxides, which should be taken into account when designing technologies for groundwater treatment.
Keywords: флуктуация; техногенные образования; угольные шахты; Приморский край; колебания; гидрогеохимические процессы; природно-техногенные комплексы; грунтовые воды